Genetically Predicted Atrial Fibrillation and Valvular Heart Disease: A Two-Sample Mendelian Randomization Study - Gao, Jie; Bai, Yulin; Ji, Hongwen (Frontiers in Cardiovascular Medicine, 2022)
Background Previous studies have found atrial fibrillation (AF) is associated with valvular heart disease (VHD). However, whether there is a causal relationship between these two diseases or it is just a result of bias caused by confounding factors is uncertain. This study aims to examine the potential causal association between AF and VHD by using Mendelian randomization. Methods In order to examine the causal relationship between AF and VHD, we performed a two-sample Mendelian randomization study by collecting exposure and outcome data from genome-wide association study (GWAS) datasets. We utilized data from FinnGen project (FinnGen, 11,258 cases for VHD including rheumatic fever, 3,108 cases for non-rheumatic VHD, and 75,137 cases for participants) and European Bio-informatics Institute database (EBI, 55,114 cases for AF and 482,295 cases for participants). Inverse-variance weighted (IVW), MR-Egger, and weighted median approaches were performed to estimate the causal effect. Results The Mendelian randomization analysis indicated that AF increased the risk of VHD by all three MR methods [For VHD including rheumatic fever: IVW, odds ratio (OR) = 1.255; 95% confidence interval (CI), 1.191~1.322; p = 1.23 × 10−17; Weighted median, OR = 1.305, 95% CI, 1.216~1.400, p = 1.57 × 10−13; MR-Egger, OR = 1.250, 95% CI, 1.137~1.375, p = 1.69 × 10−5; For non-rheumatic VHD: IVW, OR = 1.267; 95% CI, 1.169~1.372; p = 6.73 × 10−9; Weighted median, OR = 1.400; 95% CI, 1.232~1.591; p = 2.40 × 10−7; MR-Egger, OR = 1.308; 95% CI, 1.131~1.513; p = 5.34 × 10−4]. After the one outlier SNP was removed by heterogeneity test, the results remained the same. No horizontal pleiotropic effects were observed between AF and VHD. Conclusions Our study provides strong evidence of a causal relationship between AF and VHD. Early intervention for AF patients may reduce the risk of developing into VHD.